Deploying WLAN service with OpenFlow technology. Issue 3 (8th March 2017) - Hsu, Huai‐Wen; Huang, Kuei‐Li; Kao, Yi‐Chih; Tsai, Shi‐Chun; Lin, Yi‐Bing; Batalla, Jordi Mongay; Mastorakis, George; Mavromoustakis, Constandinos X.
Summary: In this paper, we proposed a feasible software‐defined networking (SDN) wireless local area network (WLAN) solution that leverages OpenFlow technique and provides affordable centralized WLAN service without the proprietary restrictions of centralized thin access point WLAN architecture. On the basis of an SDN‐enabled WLAN architecture with fat access points, we implement and deploy a wireless network test bed, where network administrators can exploit the extensibility and flexibility of OpenFlow‐based SDN switches and controller. Service providers can develop customized application modules and required features. We build our system with open sources and commercial off‐the‐shelf hardware and develop a mechanism to control wireless bandwidth. Field experimental results show that our SDN wireless bandwidth control application can effectively manage bandwidth in a dynamic and flexible way via the SDN WLAN. Abstract : With the benefit of the extensibility and flexibility of OpenFlow‐based software‐defined networking switches and controller, we implement and deploy a wireless network. Service providers can develop customized application modules and required features. We build our system with open sources and commercial off‐the‐shelf hardware.